2021
DOI: 10.1042/bsr20211577
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of ribosomal proteins in human cancers

Abstract: The ribosome, the site for protein synthesis, is composed of ribosomal RNAs (rRNAs) and ribosomal proteins (RPs). The latter have been shown to have many ribosomal and extra-ribosomal functions. RPs are implicated in a variety of pathological processes, especially tumorigenesis and cell transformation. In this review, we will focus on the recent advances that shed light on the effects of RPs deregulation in different types of cancer and their roles in regulating the tumor cell fate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 139 publications
(174 reference statements)
1
40
0
Order By: Relevance
“…The ribosomal protein S6's phosphorylation in response to numerous growth factors has been discovered as a growth regulator, whereas some roles of other ribosomal proteins are not recognized [ 17 , 18 ]. Ribosomal proteins are overexpressed in breast cancer, liver, and colon [ 19 ]. Increased cell proliferation or development does not immediately increase ribosomal protein mRNA [ 20 ] immediately.…”
Section: Introductionmentioning
confidence: 99%
“…The ribosomal protein S6's phosphorylation in response to numerous growth factors has been discovered as a growth regulator, whereas some roles of other ribosomal proteins are not recognized [ 17 , 18 ]. Ribosomal proteins are overexpressed in breast cancer, liver, and colon [ 19 ]. Increased cell proliferation or development does not immediately increase ribosomal protein mRNA [ 20 ] immediately.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found GLUD2, a potentially relevant gene for HCC (47). In one study, overexpression of RPL39 was reported to be associated with HCC (48). In one study, KDELR2 was identified as a potential gene associated with HBV (49).…”
Section: Discussionmentioning
confidence: 98%
“…RPLs may be able to induce oncogenesis through their extra-ribosomal functions. Overactivity of ribosome biogenesis is crucial to the initiation and progression of cancer [23].RPLs' pattern of expression varies considerably between tumor types and tissues, suggesting that they can be used as biomarkers for a variety of cancers [24]. The ribosomal protein gene 5 (RPL5) was reported to be signi cantly mutated in glioblastoma, melanoma, and breast cancer samples as a haploinsu cient tumor suppressor [25].…”
Section: Discussionmentioning
confidence: 99%